MULTICULTURAL BASED-ISLAMIC EDUCATION LEARNING PLANNING - Mumtahanah, Mumtahanah; Sumiati, Sumiati; Rosmiati, Rosmiati (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Background: Various previous studies have responded to the study of multicultural education. However, the focus on the application of multicultural-based Islamic education learning planning steps has not been examined in depth by previous research. Purpose: The purpose of this study is to determine how Islamic education lessons that are multiculturally based are planned. Method: The research methodology employed is library research, which entails gathering data from a variety of sources, including books and periodicals that are relevant to study issues. Result: The study's findings indicate that there are multiple steps involved in implementing a multicultural Islamic education curriculum. The first is switching to a progressive curriculum philosophy, such as social reconstruction, progressivism, or humanism, for the curriculum. Second, the learning theory that is employed no longer has to be limited to specific psychological theories of learning; it also needs to take into consideration the diversity of social, cultural, political, and economic contexts. Third, group learning and competitive learning in a favorable environment take the role of the traditional learning process. Fourth, the assessment method must take into account every facet of the student's aptitudes and character, in line with the goals and subject matter being created. Conclusion: Through this research, conceptual implications are obtained in the form of multicultural-based Islamic education learning complex planning, as a step towards realizing harmony and diversity in society.